Extension of Mitogenome Enrichment Based on Single Long-Range PCR: mtDNAs and Putative Mitochondrial-Derived Peptides of Five Rodent Hibernators - Emser, Sarah V.; Schaschl, Helmut; Millesi, Eva; Steinborn, Ralf (Frontiers in Genetics, 2021)
Enriching mitochondrial DNA (mtDNA) for sequencing entire mitochondrial genomes (mitogenomes) can be achieved by single long-range PCR. This avoids interference from the omnipresent nuclear mtDNA sequences (NUMTs). The approach is currently restricted to the use of samples collected from humans and ray-finned fishes. Here, we extended the use of single long-range PCR by introducing back-to-back oligonucleotides that target a sequence of extraordinary homology across vertebrates. The assay was applied to five hibernating rodents, namely alpine marmot, Arctic and European ground squirrels, and common and garden dormice, four of which have not been fully sequenced before. Analysis of the novel mitogenomes focussed on the prediction of mitochondrial-derived peptides (MDPs) providing another level of information encoded by mtDNA. The comparison of MOTS-c, SHLP4 and SHLP6 sequences across vertebrate species identified segments of high homology that argue for future experimentation. In addition, we evaluated four candidate polymorphisms replacing an amino acid in mitochondrially encoded subunits of the oxidative phosphorylation (OXPHOS) system that were reported in relation to cold-adaptation. No obvious pattern was found for the diverse sets of mammalian species that either apply daily or multiday torpor or otherwise cope with cold. In summary, our single long-range PCR assay applying a pair of back-to-back primers that target a consensus sequence motif of Vertebrata has potential to amplify (intact) mitochondrial rings present in templates from a taxonomically diverse range of vertebrates. It could be promising for studying novel mitogenomes, mitotypes of a population and mitochondrial heteroplasmy in a sensitive, straightforward and flexible manner.